2019
DOI: 10.1038/s41598-018-36896-x
|View full text |Cite
|
Sign up to set email alerts
|

Traction force microscopy with optimized regularization and automated Bayesian parameter selection for comparing cells

Abstract: Adherent cells exert traction forces on to their environment which allows them to migrate, to maintain tissue integrity, and to form complex multicellular structures during developmental morphogenesis. Traction force microscopy (TFM) enables the measurement of traction forces on an elastic substrate and thereby provides quantitative information on cellular mechanics in a perturbation-free fashion. In TFM, traction is usually calculated via the solution of a linear system, which is complicated by undersampled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(107 citation statements)
references
References 101 publications
0
82
0
Order By: Relevance
“…(2) is L2 regularization, which is also called Tikhonov regularization or ridge regression. L2 regularization is a robust procedure that suppresses noise and produces a smoothed traction field [31]. Here, the residual u − Mf…”
Section: Regularizationmentioning
confidence: 99%
See 3 more Smart Citations
“…(2) is L2 regularization, which is also called Tikhonov regularization or ridge regression. L2 regularization is a robust procedure that suppresses noise and produces a smoothed traction field [31]. Here, the residual u − Mf…”
Section: Regularizationmentioning
confidence: 99%
“…Moreover, it has also been shown that the L-curve criterion can fail systematically [43,42]. Therefore, the L-curve criterion is often complemented with other methods for finding the regularization parameter, such as cross-validation [31]. In any case, a manual parameter variation is mandatory to check the validity of the solution.…”
Section: Regularizationmentioning
confidence: 99%
See 2 more Smart Citations
“…To mitigate these problems, most conventional approaches include a regularization term in the fitting function, which decreases the noise and complexity of the solution while also limiting the 4 accuracy and resolution (2,17). An additional challenge is the difficulty to define the relative weight, represented by a parameter λ, between regularization and accuracy (18).…”
Section: Introductionmentioning
confidence: 99%